SIMULATION OF THE TEMPERATURE DEPENDENCE OF THE OSCILLATION OF MAGNETOSISTIVITY IN NANOSIZED SEMICONDUCTOR STRUCTURES UNDER THE EXPOSURE TO EXTERNAL FIELDS - R.G. Rakhimov (Web of Journals Publishing, 2024)
Recently, a number of remarkable nonequilibrium phenomena have been discovered in semiconductor structures under strong alternating and constant excitation of the electron gas. Most attention has been drawn to microwave-induced resistivity oscillations, especially after the impressive observation of "zero-resistance states" at the oscillation minima. Two mechanisms of resistivity oscillations caused by microwave radiation have been proposed, one of which arises due to oscillations in the spectral density of states of Landau levels with extended disorder. Both mechanisms reproduce the observed phase of the ω/ωc oscillations. The displacement mechanism takes into account the disorder of scattering by microwave radiation in the presence of an electric field and creates temperature-independent oscillations of resistivity caused by microwave radiation, which is contrary to experiments. On the contrary, the inelastic mechanism associated with microwave-induced oscillatory changes in the electron energy distribution gives rise to resistivity oscillations with an amplitude proportional to the inelastic scattering time.
Keywords: Semiconductor, electron gas, oscillation, microwave, Landau levels, electric field, mathematical model, Shubnikov-de Haas oscillations